Application Of Outsorching Labor Perspective Of The New Criminal Code: Application Of Outsorching Labor Perspective Of The New Criminal Code - Perdana, Surya (International Asia Of Law and Money Laundering (IAML), 2025)
The development of outsourcing practices in Indonesia faces new challenges with the enactment of a new Criminal Code that presents a different perspective in protecting outsourced workers. This study examines how the regulation of outsourced labor within the framework of the new criminal code and its juridical impact on the protection of workers involved in tripartite Labor Relations. Using normative juridical methods with a statutory and conceptual approach, this study analyzes the harmonization between the new criminal code and labor regulations governing outsourcing in Indonesia. The findings of the study show that the new penal code brings important breakthroughs through the recognition of corporations as subjects of criminal law and the application of corporate criminal liability, creating a layered protection system that integrates administrative, civil, and criminal dimensions for outsourced workers. However, the implementation of regulations still faces complexity due to the employment relationship between workers, vendors, and service user companies. Harmonization between the new criminal code with the Labor Law and the job creation law is an urgent need to close legal gaps and realize comprehensive legal certainty. The study recommends the implementation of joint liability mechanisms, strengthening the capacity of labor inspectors, and standardizing labor agreements to realize optimal protection for outsourced workers.